Development of management options for the control of aflatoxin in maize in Benin, Africa - Hell, K.; Fandohan, P.; Cardwell, K. (2002)
From 1999 till 2001, management strategies for the reduction of aflatoxin in maize were developed in participatory tests with farmers. After 6 months of storage, maize in bags contained more aflatoxin than maize in traditional farmers’ stores. Harvesting maize late increased the risk of aflatoxin contamination. Sorting out damaged maize before storage significantly decreased the levels of aflatoxin instored maize. All the management strategies were evaluated, and the economic benefit assessed against traditional farming practices. Fungal infection and insect infestation were measured and related to aflatoxin contamination. A technology package for the reduction of aflatoxin in maize will be developed for each agroecological zone in Bénin, comprising specific maize varieties, harvest timing, drying, sorting, insect control and storage technologies.